Neuropsychiatric Treatments for Epilepsy: Nonpharmacological Approaches - Lopez, Maria Raquel; Kanner, Andres M. (Seminars in Neurology, 2022)
Neuropsychiatric conditions are frequently found in patients with epilepsy (PWE). These entities can be as disabling as epilepsy resulting in a significant negative impact on the quality of life of this population if not addressed and treated appropriately. In this article, we provide an overview of non-pharmacological treatments currently available to these patients—and review their effect on mood and anxiety disorders as well as epilepsy. These treatment strategies will allow the practitioner to optimize clinical care during the initial evaluation, which begins with the recognition of the neuropsychiatric condition followed by the appropriate individualized psychotherapeutic approach and/or neuromodulation therapy. To plan a comprehensive treatment for PWE, practitioners must be familiar with these therapeutic tools. Additional clinical research is needed to further create a multidisciplinary team in the assessment and management of neuropsychiatric disorders in PWE.
Keywords: neuropsychiatry; neuromodulation; psychotherapy; vagus nerve stimulation; transcranial magnetic stimulation; electroconvulsive therapy